2019
DOI: 10.5430/ijhe.v9n1p179
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence, Work Family Conflict, and Job Satisfaction on Junior High School Teacher’s Performance

Abstract: Female workers do not always get the same rights as their male colleagues. Many women are forced to dispel their desires to become structural career women because they are unable to compete with men. Therefore, it is necessary to have clear performance measurements to prove that female teachers also have good performance. The research was conducted using explanatory research with a quantitative approach. The test was conducted by SEM analysis techniques using AMOS. The study found a significant influence betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
8
0
5
Order By: Relevance
“…Kunci perusahaan untuk dapat melayani konsumen dengan baik, salah satunya adalah aspek kepuasan kerja para karyawan (Bonn, 2018). (Wijayati et al, 2020) menyatakan bahwa kepuasan kerja ialah wujud dari perasaan karyawan yang muncul akibat faktorfaktor yang berhubungan antara pekerjaan dan kebutuhan materi dan psikologis.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Kunci perusahaan untuk dapat melayani konsumen dengan baik, salah satunya adalah aspek kepuasan kerja para karyawan (Bonn, 2018). (Wijayati et al, 2020) menyatakan bahwa kepuasan kerja ialah wujud dari perasaan karyawan yang muncul akibat faktorfaktor yang berhubungan antara pekerjaan dan kebutuhan materi dan psikologis.…”
Section: Pendahuluanunclassified
“…Raja & Ganesan Kanagaraj, (2020) mendukung hal tersebut, bahwa work life balance adalah terciptanya keseimbangan dan keterlibatan karyawan terkait waktu, dan peran antara kehidupan kerja dan nonkerja. Iswardhani et al (2019) mengatakan bahwa apabila karyawan memiliki keseimbangan kerja dan non-kerja yang tinggi yang dapat membuat mereka puas, hal tersebut akan memicu munculnya etos kerja yang tinggi, dan memberikan kontribusi yang positif, karena apabila pekerjaan yang menyita waktu lebih banyak dibanding keluarga nantinya akan memunculkan work family conflict (Wijayati et al, 2020).…”
Section: Work Life Balanceunclassified
“…For example, Obrenovic et al [ 40 ] pointed out that in a modern working environment, WFC has a negative impact on employees’ psychological safety and psychological well-being, thereby negatively affecting their job performance. Wijayati et al [ 41 ] found that job performance of junior high school teachers is affected by WFC in a negative direction. Zainal et al [ 42 ] revealed that WFC is negatively correlated with service employees’ job performance.…”
Section: Hypotheses Development and Theoretical Modelmentioning
confidence: 99%
“…Furthermore, Bardach, (2008) argues that most research conducted in emotional intelligence among headteachers seem skewed to the extent which does not include issues of human diversity. Besides, majority of the studies on emotional intelligence applied either quantitative or qualitative approach, with few mixed methods (Wijayati, Kautsar, & Karwanto, 2020). However, the fluidity nature of emotional intelligence requires the application of both the quantitative and qualitative approaches in its investigation.…”
Section: The Contextmentioning
confidence: 99%